Mission-Oriented Scorecard w publicznym systemie ochrony zdrowia (perspektywa państwa jako metaorganizacji i jednostki świadczącej usługi medyczne) - Frączkiewicz-Wronka, Aldona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The main assumption to my deliberations is a statement that organizations operating in a public sector and applying performance measurement are more capable of creating higher social values by exploiting political, physical, or institutional resources than organizations which do not implement such activities. In this article, the role of effectiveness concept in contemporary management in health care system was analyzed and specific discriminates of public management were pointed out. Additionally, Mission-Oriented Scorecard was briefly characterized as a concept having considerable value for both functioning and development for organization operating in the public health care sector. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 159-166